Let's solve each equation step by step.
1. Solve \( x^2 + 6x + 9 = 0 \)
This is a perfect square trinomial: \[ (x + 3)^2 = 0 \] Thus, the solution is: \[ x = -3 \]
2. Solve \( 16x^2 - 49 = 0 \)
This is a difference of squares: \[ (4x)^2 - 7^2 = 0 \] Factoring gives us: \[ (4x - 7)(4x + 7) = 0 \] Setting each factor to zero:
- \( 4x - 7 = 0 \) → \( 4x = 7 \) → \( x = \frac{7}{4} \)
- \( 4x + 7 = 0 \) → \( 4x = -7 \) → \( x = -\frac{7}{4} \)
The solutions in fraction form, listed from smaller to larger, are: \[ x = -\frac{7}{4} \quad \text{and} \quad x = \frac{7}{4} \]
3. Solve \( 3x^2 + 18x + 24 = 0 \)
We can use the quadratic formula \( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \), where \( a = 3, b = 18, c = 24 \).
Calculate the discriminant: \[ b^2 - 4ac = 18^2 - 4(3)(24) = 324 - 288 = 36 \] Now substituting back into the quadratic formula: \[ x = \frac{-18 \pm \sqrt{36}}{2(3)} = \frac{-18 \pm 6}{6} \] Calculate the two solutions:
- \( x = \frac{-18 + 6}{6} = \frac{-12}{6} = -2 \)
- \( x = \frac{-18 - 6}{6} = \frac{-24}{6} = -4 \)
The solutions, listed from smaller to larger, are: \[ x = -4 \quad \text{and} \quad x = -2 \]
4. Solve \( 2x^2 + x - 5 = 0 \)
Using the quadratic formula again: \[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}, \quad a = 2, b = 1, c = -5 \] Calculate the discriminant: \[ b^2 - 4ac = 1^2 - 4(2)(-5) = 1 + 40 = 41 \] Substitute into the formula: \[ x = \frac{-1 \pm \sqrt{41}}{4} \] Calculating both solutions:
- \( x = \frac{-1 + \sqrt{41}}{4} \)
- \( x = \frac{-1 - \sqrt{41}}{4} \)
Approximating the second solution (using \( \sqrt{41} \approx 6.4 \)): \[ x \approx \frac{-1 - 6.4}{4} \approx \frac{-7.4}{4} \approx -1.85 \]
Now let’s calculate the first solution: \[ x \approx \frac{-1 + 6.4}{4} \approx \frac{5.4}{4} \approx 1.35 \]
The solutions, rounded to the hundredths and listed from smaller to larger, are: \[ x \approx -1.85 \quad \text{and} \quad x \approx 1.35 \]
5. Find the zeros of \( y = 2x^2 + 7x \)
To find the zeros, set \( y = 0 \): \[ 2x^2 + 7x = 0 \] Factoring out \( x \): \[ x(2x + 7) = 0 \] Setting each factor to zero:
- \( x = 0 \)
- \( 2x + 7 = 0 \) → \( 2x = -7 \) → \( x = -\frac{7}{2} \)
The zeros, listed from smaller to larger, are: \[ x = -\frac{7}{2} \quad \text{and} \quad x = 0 \]
Summary of Solutions:
- \( x = -3 \)
- \( x = -\frac{7}{4} \) and \( x = \frac{7}{4} \)
- \( x = -4 \) and \( x = -2 \)
- \( x \approx -1.85 \) and \( x \approx 1.35 \)
- \( x = -\frac{7}{2} \) and \( x = 0 \)